Ricketts' cephalogram norms observed in children from Matanzas - Heberto Conde Suárez; Federico Valentín González; Juana María Sánchez Gay (Editorial Ciencias Médicas, 2014)
Introduction: the study of the growth and development processes allows identifying and making diagnosis of anomalies to determine as early as possible the most adequate treatment, with the criteria of preventing malocclusions with skeletal characteristics from turning into more serious problems of difficult solution and prognosis in the future. Objective: to determine the mean values of Rickett's cephalogram in nine years-old children. Method: a development research was conducted in children from Matanzas and Cardenas. The universe of study was 1128 children and the final sample of 103 children with normal occlusion was selected by the stratified cluster sampling; they were analyzed using Ricketts' cephalogram. Mean t Test was used to determine values of the study variables, which showed statistically significant differences in comparison with Ricketts's variables. Results: it was proved that just four variables showed means equal to the Ricketts's norms. Conclusions: Four variables showed values similar to those of Ricketts's variables. The other nine were significantly different from those of Rickett's cephalogram. Keywords: cephalometry, Ricketts' cephalogram, normal dental occlusion, mixed dentition.